6
$\begingroup$

Here I go :

$3 + 5 + 6 = 15 \ 18 \ 72$
$5+ 5 + 6 = 25 \ 30 \ 94$
$5 + 6 + 7 = 30 \ 35 \ 85$
$5 + 5 + 3 = 25 \ 15 \ 73$
$9 + 4 + 7 = 36 \ 63 \ ? $

Replace ? with appropriate number

$\endgroup$
1
  • $\begingroup$ Do you mean digit or number? $\endgroup$
    – M Oehm
    Commented Jul 14, 2016 at 7:06

2 Answers 2

19
$\begingroup$

Answer is

$29$

Explanation:

The formula is:
$a + b + c = a*b \quad a*c\quad ((a*b) + (a*c)) - c$

Take the example of the first row
$3 + 5 + 6 = 15$ $18$ $72$
Let $a = 3, b = 5 , c = 6$

$((3*5) + (3*6)) - 6 \Rightarrow (15 + 18) - 6 \Rightarrow 33 - 6 \Rightarrow 27$
Reverse of $27$ is $72$

In the same way for the last row
For $9 + 4 + 7 = 36$ $63$ $?$

$((9*4) + (9*7)) - 7 \Rightarrow (36 + 63) - 7 \Rightarrow 99 - 7 \Rightarrow 92$
reverse of $92$ is $29$

$\endgroup$
0
$\begingroup$

for the missing value

173.32

because

for the third column I get $$26.4 * a - 0.6*b + 7c -3.08ab$$

$\endgroup$
2
  • 3
    $\begingroup$ I thinnk you are unnecessarily making it more difficult. $\endgroup$
    – Heisenberg
    Commented Jul 15, 2016 at 2:36
  • 1
    $\begingroup$ simpler or more complex is in the eye of the beholder. $\endgroup$
    – Jasen
    Commented Jul 15, 2016 at 2:37

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.